1995
DOI: 10.1007/bf00174042
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and molecular characterization of a plasmid localized in Buchnera sp. bacterial endosymbiont of the aphid Rhopalosiphum padi

Abstract: We have identified and completely sequenced a novel plasmid isolated from the aphid Rhopalosiphum padi. Evidence which suggests that the plasmid occurs localized within the bacterial endosymbionts is presented. The plasmid contains the four genes that constitute the entire leucine operon. This fact makes it really unique since most plasmids are dispensable and lack genes that encode essential anabolic functions. Four more phloem-feeding aphid species also seem to contain homologous plasmids. Although further w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
85
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 30 publications
(31 reference statements)
4
85
0
Order By: Relevance
“…A recent study found congruence of gene genealogies in Buchnera of Uroleucon ambrosiae, suggesting strictly vertical transfer even within the same host species (22). These results support previous conclusions of congruence among Buchnera genealogies and contribute to the larger picture of vertical plasmid transmission across millions of years (5,6,10,48,49,52,63,64). Our data suggest that the single proposed instance of plasmid transfer in Buchnera may represent a very rare event that occurred early in the evolution of the Pemphigidae (62).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…A recent study found congruence of gene genealogies in Buchnera of Uroleucon ambrosiae, suggesting strictly vertical transfer even within the same host species (22). These results support previous conclusions of congruence among Buchnera genealogies and contribute to the larger picture of vertical plasmid transmission across millions of years (5,6,10,48,49,52,63,64). Our data suggest that the single proposed instance of plasmid transfer in Buchnera may represent a very rare event that occurred early in the evolution of the Pemphigidae (62).…”
supporting
confidence: 90%
“…In contrast to facultative symbionts such as Rhizobium and Vibrio, lateral gene transfer in Buchnera may be highly constrained since this obligate symbiont spends its entire life cycle within specialized host cells (bacteriocytes) (11,43). In accordance with this hypothesis, several previous studies show phylogenetic congruence among chromosomal (trpB and 16S rRNA) and plasmid (trpEG and leuABCD) genes of Buchnera associated with the family Aphididae and suggest a lack of plasmid transfer in this symbiont group (5,6,10,22,48,49,51,63,64). However, recent work suggests horizontal transfer of the plasmid-encoded repA1 gene in Buchnera of Pemphigus spyrothecae (62).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…During this coevolutionary process, Buchnera suffered considerable genomic changes (i.e., a great reduction in genome size, an increased AϩT bias, great accumulation of deleterious mutations, and the amplification of genes involved in amino acid biosynthesis) (16)(17)(18). Because pathogenic intracellular bacteria with small genomes display a wide variation in chromosome length, it would also be expected that Buchnera of different aphid lineages differ in genome size and gene content.…”
mentioning
confidence: 99%
“…In recent years, genes encoding key enzymes in the pathways leading to tryptophan and leucine biosynthesis (trpEG and leuABCD, respectively) were found to be translocated from the chromosome to plasmids (Lai et al, 1994;Bracho et al, 1995). Amplification of plasmids for essential amino-acid biosynthesis was considered as an indication that B. aphidicola is able to overproduce these nutrients for the benefit of its host and, hence, an adaptation to its symbiotic lifestyle.…”
Section: Leucine and Tryptophan Plasmids Go Back And Forwardmentioning
confidence: 99%